2010
DOI: 10.1074/jbc.m110.105718
|View full text |Cite
|
Sign up to set email alerts
|

Calcium as a Crucial Cofactor for Low Density Lipoprotein Receptor Folding in the Endoplasmic Reticulum

Abstract: The family of low density lipoprotein (LDL) receptors mediate uptake of a plethora of ligands from the circulation and couple this to signaling, thereby performing a crucial role in physiological processes including embryonic development, cancer development, homeostasis of lipoproteins, viral infection, and neuronal plasticity. Structural integrity of individual ectodomain modules in these receptors depends on calcium, and we showed before that the LDL receptor folds its modules late after synthesis via interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 75 publications
3
32
0
Order By: Relevance
“…The highly unsaturated, fluid environment of the ER membrane, and ER membrane-bound UPR sensor proteins may be particularly susceptible to even minor increases in the amount of saturated fatty acids (167). Another mechanism by which saturated fatty acids may disrupt ER homeostasis is through reduced ER calcium stores in liver cells, perhaps via compromised calcium-dependent ER protein chaperone function (124,172). Finally, recent data have demonstrated that saturated fatty acids increase the expression of phosphotidylinositol 3-kinase interacting protein 1, and SiRNA-mediated knockdown of this protein protected HepG2 cells from palmitate-mediated ER stress (27).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…The highly unsaturated, fluid environment of the ER membrane, and ER membrane-bound UPR sensor proteins may be particularly susceptible to even minor increases in the amount of saturated fatty acids (167). Another mechanism by which saturated fatty acids may disrupt ER homeostasis is through reduced ER calcium stores in liver cells, perhaps via compromised calcium-dependent ER protein chaperone function (124,172). Finally, recent data have demonstrated that saturated fatty acids increase the expression of phosphotidylinositol 3-kinase interacting protein 1, and SiRNA-mediated knockdown of this protein protected HepG2 cells from palmitate-mediated ER stress (27).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…For as long as proteins are in the ER, they can still unfold and aggregate, loose disulfide bonds or bound calcium ions, allowing yet another chance to reach the native conformation (Braakman et al 1992a,b;Pena et al 2010). Chaperone unfolding of terminal misfolded proteins can also render them translocation competent for eventual dislocation to the cytoplasm for proteasomal degradation through the ERAD pathway.…”
Section: Protein Folding In the Ermentioning
confidence: 99%
“…Chaperone unfolding of terminal misfolded proteins can also render them translocation competent for eventual dislocation to the cytoplasm for proteasomal degradation through the ERAD pathway. When a protein has left the ER and entered the Golgi, they are as a general rule active functional structures having passed the ER quality-control test and resistant to reduction, oxidation, calcium depletion, and ATP reduction, oxidation, and calcium and ATP depletion (Braakman et al 1992b;Tatu et al 1993;Pena et al 2010).…”
Section: Protein Folding In the Ermentioning
confidence: 99%
“…It has been shown previously that the folding of influenza virus haemagglutinin is not affected by the conditions of Ca 2+ depletion used in our experiments (Pena et al, 2010). To determine the effect of Ca 2+ depletion on the folding machinery in the ER, the folding, assembly and Golgi transport of endogenous MHC Class I molecules was studied.…”
Section: +mentioning
confidence: 99%